Alternativas para la escalabilidad de aplicaciones en plataformas web de alta concurrencia - Irey Núñez, Jorge Luis (2014)
At present, the so-called “Internet of Things” has turned indispensable the applications deployed on the Internet; the computers that act as clients are not exclusively PC’s or laptops, but also smart phones, tablets, and in general many different types of devices that run applications. This characterization of indispensable is basically associated with non-functional requirements (NFR), such as availability, scalability, and fault tolerance. This article explores from a technical point of view, a new programming paradigm that lets you build the so called reactive web applications which inherently have the event-handling characteristics, scalability, resilience and sensitivity in contrast to traditional web applications.